Central Improvement of Voltage Sags in the IEEE 33-Bus Distribution System by a Number of D-STATCOMS - Bach, Quoc Khanh (Old Journal, 2019)
The paper introduces a novel method for “central improvement” of voltage sags due to short-circuits in distribution system using multiples of D-Statcoms. D-Statcom’s effectiveness for voltage sag mitigation is modeled based on the method of Thevenin’s superimposition for the problem of short-circuit calculation in distribution systems. The paper newly considers the case of using a multiple of D-Statcoms with a proposed voltage compensating principle that can be practical for large size of distribution system. A multiple of D-Statcoms are optimally located and sized on the basis of minimizing the system bus voltage deviation with regard to the constraint of D-Statcom’s size. The paper uses the IEEE 33-buses distribution feeder as the test system for voltage sag simulation and results discussion.